LEVETINOL IN COMPLEX TREATMENT OF FOCAL EPILEPSY (EXPERIENCE OF EPILEPTOLOGIST IN OUTPATIENT NETWORK, MOSCOW) - G. G. Avakyan; M. A. Bogomazova; I. I. Zhuravleva; A. M. Ismailov; E. G. Komelkova; L. N. Lesinker; Yu. I. Logvinov; O. V. Otcheskaya; S. V. Petrov; Yu. V. Rubleva; Yu. V. Solomatin; A. M. Teplysheva; et al. (Эпилепсия и пароксизмальные состояния)
Abstract: prescription of Levetinol in regimen of integrated adjunctive therapy in 30 patients with symptomatic and cryptogenic focal forms of epilepsy with poorly controlled seizures, receiving the reference probe of antiepileptic drugs, was accompanied by the attainment of a higher therapeutic effect. Remission with an average effective dose of the drug 1437.5 mg/day was observed in 6, reduction of attacks by 75% – in 8 patients. Levetinol significantly affect the indicators of anxiety and depression in the reduction of symptoms of affective disorders.